Testing the Performance of Various Polymeric Antiscalants for Mitigation of Sb-Rich Precipitates Mimicking Stibnite-Based Geothermal Deposits. (1st August 2020) - Çiftçi, Celal; Karaburun, Emre; Tonkul, Serhat; Baba, Alper; Demir, Mustafa M.; Yeşilnacar, Mehmet İrfan
Abstract : Scaling is frequently observed in geothermal fields and reduces the energy harvesting of power plants. Recently, Sb-rich deposits have developed in many fields around the world. Various polymeric macromolecules have been used as antiscalants to mitigate the formation of scale. Testing potential commercial antiscalants in field conditions is a tedious and costly process. The artificial synthesis of geothermal deposits in the lab is a more practical and economical way to test the performance of antiscalants. This study obtained a Sb-rich deposit by refluxing SbCl3 and Na2 S·3H2 O in 18 h. The product was found to be a mixture of Sb2 O3 and Sb2 S3 . We examined the performance of antiscalants such as poly(ethylene glycol), poly(vinyl pyrrolidone), Gelatin, and poly(vinyl alcohol) of various molecular weights at 5 to 100 ppm. The formation of Sb2 S3 is suppressed in the presence of the polymeric antiscalants. The dosage was found to be critical for the solubilization of Sb-rich deposits. Gelatin of 5 ppm showed the highest performance under the conditions employed in this study. While low dosages improve the concentration of [Sb 3+ ], high dosages are required to increase the solubility of [S 2- ]. Moreover, the amount of deposit is reduced by 12.4% compared to the reference (in the absence of any polymeric molecules). Thus, comparatively, Gelatin shows the most promising performance among the molecules employed.